Utilization of Digital Technology in Handling Schizophrenia: A Literature Study - Kurniawan Kurniawan; Sri Rahayu; Rahmah Tresnala; Toni Arisandi; Ai Indah Nazriah; Khoirunnisa Khoirunnisa; Efri Widianti; Nurlaila Fitriani (Jurnal Berita Ilmu Keperawatan, 2022)
In the modern era, digital technology is widely found and used by people because it is easy to access. The use of digital technology-based interventions on psychosis problems can increase cost-effectiveness because patients do not have to go to hospitals or clinics for treatment. The literature study aimed to identify the use of digital technology in the management of schizophrenia. The research method used the PICO with the keyword using in Indonesian and English "Patients and Families AND Digital Technology AND Control of Psychosis Patients' Symptoms" in the period 2011-2021, Indonesian and English, full-text literature, original research, focused on digital technology schizophrenia and individual and family sample populations. The results of the search for articles in the literature study found 12 articles that were relevant to the main topic. The study results showed that digital technology affects the care process for schizophrenics and is also useful for families as caregivers. Using digital technology, actions that can be done are psychoeducation, behavior change, prevention strategies, and good handling interventions. The implementation of digital technology measures provides comprehensive benefits and easy access through both the web and the application.